PENERAPAN STRATEGI PEMBELAJARAN GO TO YUOR POST UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS VI SDN 024 TARAI BANGUN KECAMATAN TAMBANG KABUPATEN KAMPAR - Delfi Yendri (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2017)
This research is motivated by the poor results of Study Social Sciences (IPS) Student Class VI SDN 024 Tarai Bangun Kecamatan Tambang. This study aims to determine the resulting increase studying social sciences (IPS) student class VI SDN 024 Tarai Bangun Kecamatan Tambang through the application of learning strategies go to yuor post, which carried out for 1 month. The subjects were VI SDN 024 Tarai Bangun Kecamatan Tambang by the number of students as many as 38 people. Form of research is classroom action research. The research instrument consists of instruments and instrument performance data collection activity observation sheet form teacher and student activity. Based on the research, the conclusion to this study is based on the analysis and discussion in chapter IV can be concluded that the application of learning strategies go to yuor post can improve learning outcomes in the subject of social sciences grade VI SDN 024 Tarai Bangun Kecamatan Tambang. Evidenced by the increase in learning outcomes before action to the first cycle, to cycle II. Before the act of student learning outcomes classified as unresolved with an average of 59%, an increase in the first cycle by an average of 69%. While the results of student learning in the second cycle must be increased by an average of 75% with the category completed.